2023
DOI: 10.3390/ijms24076800
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers in the Diagnosis and Prognosis of Rheumatoid Arthritis–Associated Interstitial Lung Disease

Abstract: Objectives: to identify inflammatory factors and soluble cytokines that act as biomarkers in the diagnosis and prognosis of rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Methods: we performed a nested prospective observational case–control study of patients with RA-ILD matched by sex, age, and time since the diagnosis of RA. All participants underwent pulmonary function testing and high-resolution computed tomography. ILD was defined according to the criteria of the American Thoracic Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The study found higher disease activity, according to the Disease Activity Score with Erythrocyte Sedimentation Rate (DAS28-ESR), to be a constant in patients with RA-ILD, as well as higher titers of anti-citrullinated peptide antibodies (ACPA). This data are in line with results from various other studies [1]. Several cytokines and chemokines, such monocyte chemoattractant protein 1 (MCP-1), also known as C-C motif ligand 2 (CCL2), stromal cell-derived factor 1 alpha (SDF-1 alpha), and interleukin-18 (IL-18), were investigated for their correlation with RA-ILD.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The study found higher disease activity, according to the Disease Activity Score with Erythrocyte Sedimentation Rate (DAS28-ESR), to be a constant in patients with RA-ILD, as well as higher titers of anti-citrullinated peptide antibodies (ACPA). This data are in line with results from various other studies [1]. Several cytokines and chemokines, such monocyte chemoattractant protein 1 (MCP-1), also known as C-C motif ligand 2 (CCL2), stromal cell-derived factor 1 alpha (SDF-1 alpha), and interleukin-18 (IL-18), were investigated for their correlation with RA-ILD.…”
supporting
confidence: 87%
“…In a nested prospective observational case-control study, Mena-Vázquez et al [1] analyzed various potential biomarkers that may change the approach to the diagnosis and follow-up of rheumatoid arthritis-interstitial lung disease (RA-ILD) and lessen the respiratory burden of rheumatoid arthritis (RA). The authors evaluated the cytokine and inflammation levels in patients diagnosed with RA-ILD compared to patients with RA, but not interstitial lung disease (ILD).…”
mentioning
confidence: 99%
“…Chen et al showed that the baseline titers of RF were significantly higher in patients with progressive RA-ILD, and changes in serum levels of CXCL11 and MMP-13 over 5 years were significantly associated with the progression of RA-ILD [73]. Identifying RA-ILD patients with a progressive phenotype at an early stage can be facilitated through the identification of elevated anti-citrullinated peptide antibody (ACPA) levels, since its presence is associated with high morbidity and mortality [105]. In addition, KL-6 is a circulating marker that is also relevant for diagnosis and for progression in patients with RA-ILD.…”
Section: Ctd-ildsmentioning
confidence: 99%
“…Regarding other cytokines, IL-4 and IL-18 are also elevated in the serum of patients with ILD [42,158]. In addition, IL-13 is high, being associated with lung fibrosis in HRCT [159][160][161][162][163].…”
Section: Tnf-αmentioning
confidence: 99%